How musical was my valley? Exploring resources and relationships in local popular music-making between 1996 and 2006. (21st January 2020) - Cleaton, Anne
Abstract : Influenced by the work of Howard Becker and Ruth Finnegan, this article incorporates an ethnographicapproach combined with concepts from social network theory to investigate the historicalimpacts of 'musical networks' on the town of Aberdare, between 1996 and 2006. Focusingspecifically on the local music scene, via a series of interviews, the article uncovers various strategicconnections between the conventions and understandings of the musical community, such as generationally passing down information, musical tastes and values, and local musicalhierarchies. After briefly describing the positioning and social construction of Aberdare withinthe Welsh Valleys, the article proceeds to investigate the motivations of the community to participatein popular music, in addition to the historical significance of material resources such astransport links, venues and rehearsal rooms.